If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 1) = x + 10 Reorder the terms: 4(1 + x) = x + 10 (1 * 4 + x * 4) = x + 10 (4 + 4x) = x + 10 Reorder the terms: 4 + 4x = 10 + x Solving 4 + 4x = 10 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + 4x + -1x = 10 + x + -1x Combine like terms: 4x + -1x = 3x 4 + 3x = 10 + x + -1x Combine like terms: x + -1x = 0 4 + 3x = 10 + 0 4 + 3x = 10 Add '-4' to each side of the equation. 4 + -4 + 3x = 10 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 10 + -4 3x = 10 + -4 Combine like terms: 10 + -4 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| 20=11+4(x+1) | | 2(2h+1)=22 | | -x-5=2 | | 97-6x=21x+19 | | 10-9x=34-16x | | -4(y+1)=2(1-2y)-6 | | 4x+13=12x+7 | | 7x+4x+7=7 | | 7x-10y=-24 | | 4w^2-w(2w-3)= | | 3y=y+78 | | .66(6x-15)=.5(10x-4) | | 24=2(5+y) | | -2x+7-3x=-23 | | .5+2=5+0.83333333k | | (5m-6)(2m+1)= | | 3x=(4x-21) | | 5+2x+2x=13 | | 5a^4-(15a^3)+(35a^2)=0 | | 6+x+x=16 | | 8+6n=4n+4 | | 3(v-2)+5=2(3v-5) | | x^3+4x^2-9x=36 | | 4x+5x-8=46 | | 3x-3=5-x | | 7x-5=-3.5 | | 7x-37=5-13 | | 6-x=3x+22 | | 5c+15=25 | | y=4x-17-2y | | 5x-10+12x-14=180 | | 4y+2=3y-6 |